The guanylate cyclase C agonist linaclotide ameliorates the gut–cardio–renal axis in an adenine-induced mouse model of chronic kidney disease. Issue 2 (14th August 2019) - Nanto-Hara, Fumika; Kanemitsu, Yoshitomi; Fukuda, Shinji; Kikuchi, Koichi; Asaji, Kei; Saigusa, Daisuke; Iwasaki, Tomoyuki; Ho, Hsin-Jung; Mishima, Eikan; Suzuki, Takehiro; Suzuki, Chitose; Tsukimi, Tomoya; et al.
Abstract: Background: Cardiorenal syndrome is a major cause of mortality in patients with chronic kidney disease (CKD). However, the involvement of detrimental humoral mediators in the pathogenesis of cardiorenal syndrome is still controversial. Trimethylamine- N -oxide (TMAO), a hepatic metabolic product of trimethylamine generated from dietary phosphatidylcholine or carnitine derived by the gut microbiota, has been linked directly with progression of cardiovascular disease and renal dysfunction. Thus, targeting TMAO may be a novel strategy for the prevention of cardiovascular disease and chronic kidney disease. Methods: Linaclotide, a guanylate cyclase C agonist, was administered to adenine-induced renal failure (RF) mice and changes in renal function and levels of gut-derived uremic toxins, as well as the gut microbiota community, were analyzed using metabolomic and metagenomic methods to reveal its cardiorenal effect. Results: Linaclotide decreased the plasma levels of TMAO at a clinically used low dose of 10 μg/kg in the adenine-induced RF mouse model. At a high concentration of 100 μg/kg, linaclotide clearly improved renal function and reduced the levels of various uremic toxins. A reduction in TMAO levels following linaclotide treatment was also observed in a choline-fed pro-atherosclerotic model. Linaclotide ameliorated renal inflammation and fibrosis and cardiac fibrosis, as well as decreased the expression of collagen I, transforming growth factor-β, galectin-3 (Gal-3) and ST2 genes. Plasma levels of Gal-3 and ST2 were also reduced. Because exposure of cardiomyocytes to TMAO increased fibronectin expression, these data suggest that linaclotide reduced the levels of TMAO and various uremic toxins and may result in not only renal, but also cardiac, fibrosis. F4/80-positive macrophages were abundant in small intestinal crypts in RF mice, and this increased expression was decreased by linaclotide. Reduced colonic claudin-1 levels were also restored by linaclotide, suggesting that linaclotide ameliorated the 'leaky gut' in RF mice. Metagenomic analysis revealed that the microbial order Clostridiales could be responsible for the change in TMAO levels. Conclusion: Linaclotide reduced TMAO and uremic toxin levels and could be a powerful tool for the prevention and control of the cardiorenal syndrome by modification of the gut–cardio–renal axis.